Desafíos de Brasil para la consolidación de su protagonismo internacional: educación y cultura - Rocha, Elizabete Sanches [UNESP] (2012)
Over the last years, Brazil has gained international visibility especially due to the capacity of its economical development and the progress of its public policies on fighting poverty. Though there reason for celebration exists with respect to the country’s recent achievements, Brazil still has a lot to do if it wants to gain international prominence. In this paper, we address two issues that are fundamental for Brazil to achieve real leadership: education and culture.